Terrorism, Crime, and Public Policy - Forst, Brian (Cambridge University Press, 2013)
Terrorism was a fringe subject in the fields of criminal justice, political science, public administration, and public policy prior to the terrorist attacks of September 11, 2001. Suddenly, it emerged as the most critical problem of our time. The 9/11 disaster shocked, mystified, and angered people. It awakened us to the reality of a world becoming more aware of itself and more connected than ever before and, at the same time, much more perilous. Although the shock has subsided – at least, until the next such event – much of the mystery and confusion remains. This textbook aims to demystify the event and its aftermath and provide clarity about the prospects for public interventions and private initiatives and actions that may serve to prevent further acts of terrorism.